2015
DOI: 10.1177/1541931215591350
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclist Behavior at Stop Signs

Abstract: Unobtrusive observations of bicyclists were conducted at two-way, three-way, and four-way stop-controlled intersections. Consistent with previous reports, most cyclists did not stop at the stop sign.However, most cyclists did exhibit safety-related behaviors by making accommodations for traffic conditions. It was found that the cyclists conducted precautionary visual search when approaching stop signs, and that they were more likely to slow substantially or stop if cross traffic was not controlled by stop sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…To further study their perception and cognitive states, human sensing devices (e.g. physiology devices) have shown to provide promising insights (Ridel et al 2018;Trefzger et al 2018;Ayres et al 2015). There are practical concerns about the data collection of human sensing on real roads.…”
Section: Integration Of Human Sensing Within Ivementioning
confidence: 99%
“…To further study their perception and cognitive states, human sensing devices (e.g. physiology devices) have shown to provide promising insights (Ridel et al 2018;Trefzger et al 2018;Ayres et al 2015). There are practical concerns about the data collection of human sensing on real roads.…”
Section: Integration Of Human Sensing Within Ivementioning
confidence: 99%
“…The studies investigated how cyclists behave at stop signs. It was consistently found that cyclists rarely or never stop at stop signs (Ayres et al, 2015;Silva, 2015) In addition, various studies have shown how cyclists behave at the stop line when it is in front of the stop line of motorised traffic (Loskorn, 2010;Mangundu & Koorey, 2010). Bicycle boxes in front of or next to the stop line of motorised traffic can increase cyclists' sense of safety and cyclists are more visible to motorists.…”
Section: Introductionmentioning
confidence: 99%